Polymorphism of Rs1800629 Gene of TNF-α in the Pathogenesis of Acne Vulgaris (Global Journal of Medical Research, 2024)
Background The study of the association between acne vulgaris and the TNF- gene polymorphism rs1800629 in the Uzbek population is discussed in this article Methodology The research was conducted on 165 patients with various clinical forms of acne vulgaris and 161 healthy donors Findings During this research allele frequencies and genotypes of rs1800629 polymorphism of TNF- gene were found with statistically significant differences between the control group and subgroups of patients with acne vulgaris As a result of the investigation it was discovered that heterozygous genotype G A should be a genetic marker for an increased risk of acne development whereas homozygous genotype G G should be a marker for a reduced risk of acne formation
Keywords: acne vulgaris; TNF-α; gene polymorphism